Asset Prices When Investors Underestimate Discount Rate Dynamics - Renxuan, Wang (The Review of Asset Pricing Studies, 2026)
Underestimating discount rate volatility leads to asset pricing anomalies. Using analysts’ return forecasts as proxies for subjective discount rates, I show that these forecasts exhibit systematically lower volatility than CAPM-based benchmarks, whose objective fluctuations negatively predict future returns, especially for high beta-volatility stocks. A misvaluation measure based on this underestimation significantly predicts cross-sectional CAPM alphas, while a tradable factor explains 12 prominent anomalies. These findings underscore discount rate volatility underestimation as a unifying explanation for analysts’ forecast errors and cross-sectional return predictability, linking recent evidence on aggregate subjective belief dynamics with firm-level mispricing.